1982
DOI: 10.1007/bf00200748
|View full text |Cite
|
Sign up to set email alerts
|

R�ntgenkontrastgebender Mageninhalt bei suicidaler Trichlorethylen-Vergiftung

Abstract: A lethal case of trichlorethylene poisoning is reported. A 50-year-old woman had drunk some 100 ml of pure trichlorethylene. The trichloracetic acid found only in traces in her urine indicated that death apparently occurred very rapidly. Furthermore, substances contained in the hair tonic "K5-Tinktur" were found in remnants of the corps in safekeeping. Skin burns around the mouth, and also on the mucous membrane of the vestibule of the mouth, were striking. The special odor during the autopsy indicated poisoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Several research groups have recently been enhancing the speed of AFM for the imaging of dynamic processes, mostly in the field of biophysics, with impressive results. [13][14][15][16] In these cases, the sample size is usually very small, e.g., a few mm, and the sample has small height corrugations. This makes "sample scanning" design a suitable architecture, in which the AFM cantilever is kept stationary and the sample is scanned along three axes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several research groups have recently been enhancing the speed of AFM for the imaging of dynamic processes, mostly in the field of biophysics, with impressive results. [13][14][15][16] In these cases, the sample size is usually very small, e.g., a few mm, and the sample has small height corrugations. This makes "sample scanning" design a suitable architecture, in which the AFM cantilever is kept stationary and the sample is scanned along three axes.…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups have suggested parallelization of AFM as a direct approach to increasing AFM throughput in direct proportion to the number of AFM tips in an array. 12,[14][15][16][17][18] Following this path, efforts to increase the throughput of AFM using arrays of cantilevers have been made, instead of a single cantilever, motivated by advances in microsystems fabrication 3 technologies and CMOS processes. Examples include data storage, 18 parallel imaging and force spectroscopy 12 and parallel AFM nanolithography.…”
Section: Introductionmentioning
confidence: 99%